Effervescent tablets of tobacco leaves (nicotiana tabacum l.) potential as denture cleansers - Dewi Kristiana; Ady Soesetijo; Gunadi; Rahardyan Parnaadji; Amiyatun Naini (DiscoverSys Inc., 2022)
Objective: Poor denture hygiene could be a risk factor for denture stomatitis. Tobacco leaves (Nicotiana tabacum L.) can be used as a base for denture cleaning because tobacco leaves contain ingredients that are antibacterial and antifungal. Is there any effect of tobacco leaf extract (Nicotiana tabacum L.) effervescent tablets with a concentration of 25%, 50%, 75%, as an acrylic resin denture cleaner on the growth of C albicans and an effective concentration in the formulation of tobacco leaf extract effervescent tablets as a acrylic resin denture cleaner against the growth of C.albicans Material and Methods: The type of this research is a laboratory experimental study with a randomized posttest only control group design. The samples were divided into 5 sample groups, namely: acrylic plate immersed in Effervescent tablet of tobacco leaf extract with a concentration of 25%, 50%, 75% for 30 minutes, acrylic plate for the commercially sold effervescent tablet for 20 minutes and acrylic plate immersed in distilled water for 30 minutes. The acrylic resin plate contaminated with C.albicans was then measured using a spectrometer to see the turbidity. Then the data analyzed using one way ANOVA. Result: There were significant differences in all groups, except for the effervescent tablets of tobacco leaf extract (nicotiana tabacum L.) with 75% concentration and commercially sold denture cleanser effervescent tablets which was .473. There was no significant difference. Conclusion: Effervescent tablets of Tobacco leaf (Nicotiana tabacum L.) are 75% effective in inhibiting C.albicans with immersion time of 30 minutes.